MANAGEMENT OF ECTOPIC PREGNANCY WITH HYPOVOLEMIC SHOCK GRADE III FROM THE SIDE OF ANESTHESIOLOGY - eka Cania; Bambang Eko Subekti (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Ectopic pregnancy occurs when the conceptus implants outside the normal endometrium. Critical situation can occur if the ectopic pregnancy causes abortion or tubal rupture. About 16% of deaths by severe bleeding (hemorrhagic) in pregnancy is reported to be caused by a ruptured ectopic pregnancy. Hypovolemic shock is a shock that occurs due to a reduction in intravascular plasma volume. This shock, in ruptured ectopic pregnancy case, may occur as a result of hemorrhagic. Mrs. N, 29 years old, was taken to the hospital with complaints of lower abdominal pain accompanied by vaginal bleeding since 2 days before hospital admission. Thepatient had no menstrual periods since 2 months ago and was confirmed pregnant by a pregnancy test. On arriving at the hospital, the patient in a state of compos mentis that confirmed with the Glasgow Coma Scale (GCS) was 15, blood presure was 110/50 mmHg, pulse rate was 120x/min, respiratory rate was 24x/min, temperature was 36,0ºC, which were drasticly change into shock in one hour later. Physical examination found tenderness and rebound tenderness in the suprapubic region (+). Gynecological examination found livide portio, closed Orificium Externum Uteri (OEU), flour (-), fluxus (+), no active vaginal bleeding. In vaginaltoucher found vaginal mucosa palpabled smooth, lower portio palpabled soft, closed OEU, right-left AP palpabled tense, painful shake portio (+), prominent douglas cavity, culdocentesis found blood. Superior and inferior extremities felt cold (+/+), no cyanosis, good turgor, capilary refill time (CRT)>2 seconds. Laboratory examination obtained Hb 5.5 g/dl, hematocrit 15%, leukocytes 24,500/ul. This patient was diagnosed with ruptured ectopic pregnancy with hypovolemic shock grade III and was treated with fluid resucitation then emergency laparotomy. This condition has dubia ad malam prognosis, because it is determined by the accuracyand speed of treatment. [J Agromed Unila 2014; 1(3):202-206]Keywords: fluid resuscitation, hypovolemic shock grade III, ruptured ectopic pregnancy